(untitled) (The Peerian Journal, 2025)
This article analyzes the experience of developing and introducing new technologies in the production sector of cooperative enterprises operating in Uzbekistan during the years of Soviet power. The gradual development of rationalization and inventive movements during this period is studied. Also, the unique aspects of the activity of the handicraft cooperative and its role in solving the socio-economic problems of the country are highlighted. The article was prepared on the basis of archival sources.